Detection of Hg2+ and F− Ions by Using Fluorescence Switching of Quantum Dots in an Au‐Cluster–CdTe QD Nanocomposite. Issue 19 (11th March 2013) - Paramanik, Bipattaran; Bhattacharyya, Santanu; Patra, Amitava
Abstract A single probe of an Au nanocluster–CdTe quantum dots nanocomposite has been developed by using tripeptide‐capped CdTe quantum dots (QD) and bovine serum albumin (BSA) protein‐conjugated Au25 nanocluster (NC) for detection of both Hg2+ ion and F− ion. The formation of Au‐NC–CdTe QD nanocomposite has been confirmed by TEM, steady state and time resolved spectroscopy, CD and FTIR studies. A significant signal off (74 % PL quenching at 553 nm) phenomenon of this nanocomposite is observed in presence of 6.56×10−7 M Hg2+ ion, due to salt‐induced aggregation. However, a dramatic PL enhancement (128 %) of the Au‐NC–CdTe QD nanocomposite is observed in presence of 8.47×10−7 M F− anion. The calculated limit of detections (LOD) of Hg2+ ion concentration and F− ion concentration are found to be 9 and 117 nM, respectively, which are within the safety range set by the United States Environment Protection Agency. Thus, the simple Au‐NC–CdTe QD optical‐based sensor is very useful to detect both toxic cations and anions.